155 Unplanned Returns to the Operating Room Within 30 Days in Neurosurgery: Insights From a National Surgical Registry. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Kerezoudis, Panagiotis; Alvi, Mohammed Ali; Spinner, Robert J; Meyer, Fredric B; Goyal, Anshit; Yolcu, Yagiz U; Habermann, Elizabeth B; Bydon, Mohamad
Abstract: INTRODUCTION: Large-scale data on the appropriateness and utility of unplanned return to the operating room (ROR) as a quality measure in neurosurgery are scarce. METHODS: We queried the ACS-NSQIP registry for patients undergoing neurosurgical procedures during 2012-2016. The incidence, timing, and nature of 30-d unplanned ROR after major procedure groups were determined. Logistic regression was conducted to identify factors associated with 30-d unplanned ROR following the 3 most common cranial and spinal operations: craniotomy for intra-axial neoplasm, supratentorial meningioma or skull base tumors, anterior cervical discectomy and fusion, posterior lumbar decompression and posterior lumbar fusion. RESULTS: A total of 193 459 neurosurgical cases were identified, of which 7067 (3.7%) had at least 1 unplanned ROR within 30 d after the index procedure. Rates were 4.3% and 1.5% for inpatient and outpatient procedures, respectively. Median time (interquartile range) to ROR was 11 d (4-12). Overall, the most common reasons were wound complication/surgical site infection (0.7%), hematoma evacuation (0.6%), and repeat surgery (0.5%). Within inpatient cranial cases, the 3 procedures with the highest 30-d unplanned ROR rates were craniotomies for intracranial infection/abscess (14.7%) followed by subdural hematoma (14.1%), and subarachnoid hemorrhage (12.2%). Within inpatient spinal cases, the highest reoperation rates were observed among thoracic fusions (6.9%), thoracic decompressions (5.6%), and "long" deformity fusions (5%). On multivariable analysis, the relative amount of variation in reoperation risk was found to be 1 to 25% for demographics, 1 to 22% for comorbidities, 1 to 6% for preoperative lab values, and 2 to 46% for operative characteristics. CONCLUSION: Significant variations in rates of 30-d unplanned ROR exist among neurosurgical procedures. The findings may inform stakeholders on the optimal parameters that need to be taken into account when crafting, endorsing and implementing quality metrics for neurosurgery that aim to assess surgical performance and reward or penalize hospitals and providers.